Performance of individual and joint risk stratification by an environmental risk score and a genetic risk score in a colorectal cancer screening setting - Balavarca, Yesilda; Weigl, Korbinian; Thomsen, Hauke; Brenner, Hermann (International journal of cancer, 2020)
Early detection of colorectal neoplasms can reduce the disease burden of colorectal cancer by timely intervention of individuals at high risk. Our aim was to evaluate a joint environmental-genetic risk score as a risk stratification tool for early detection of advanced colorectal neoplasm (ACRN). Known environmental risk factors and high-risk genetic loci were summarized into risk scores for ACRN in 1014 eligible participants of a screening study. The performances of single and joint environmental-genetic scores were evaluated with estimates and 95% confidence intervals (CI) of the absolute risk, relative risk and predictive ability using the area under the curve (AUC). Individuals with higher environmental risk scores showed increasing ACRN risk, with 3.1-fold for intermediate risk and 4.8-fold for very high risk, compared to the very low environmental risk group. Similarly, individuals with higher genetic risk scores showed increasing ACRN risk, with 2.2-fold for intermediate risk and 3.5-fold for very high risk, compared to the lowest genetic risk group. Moreover, the joint environmental-genetic score improved the ACRN risk stratification and showed higher predictive values (AUC = 0.64; 95%CI = 0.60-0.67) with substantial difference (p = 0.0002) compared to the single environmental score (0.58; 0.55-0.62). The integration of environmental and genetic factors looks promising for improving targeting individuals at high-risk of colorectal neoplasm. Applications in practical screening programs require optimization with additional genetic and other biomarkers involved in colorectal carcinogenesis.
First published: 14 March 2019
Gesehen am 15.04.2020